2014
DOI: 10.1007/s11033-014-3059-z
|View full text |Cite
|
Sign up to set email alerts
|

Matrine inhibits proliferation and induces apoptosis of human colon cancer LoVo cells by inactivating Akt pathway

Abstract: The present study has investigated the anti-tumor activity and the underlying mechanisms of matrine on human colon cancer LoVo cells. Matrine inhibited the proliferation of the cells in dose- and time-dependent manners. The concentration required for 50 % inhibition (IC50) was 1.15, 0.738, and 0.414 mg/ml, when cell were incubated with matrine for 24, 48, and 72 h, respectively. Matrine induced cell cycle arrest at G1 phase by downregulating cyclin D1 and upregulating p27 and p21. Matrine induced cell apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Matrine has various pharmacological effects including anti-tumor activities on different cancer cell lines (Cress et al, 2000;Zhang et al, 2014). In this study, our data demonstrated the anti-proliferative effect of matrine in human NSCLC A549 cells, this is consistent with previous study (Chang et al, 2014;Zhang et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Matrine has various pharmacological effects including anti-tumor activities on different cancer cell lines (Cress et al, 2000;Zhang et al, 2014). In this study, our data demonstrated the anti-proliferative effect of matrine in human NSCLC A549 cells, this is consistent with previous study (Chang et al, 2014;Zhang et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, our data demonstrated the anti-proliferative effect of matrine in human NSCLC A549 cells, this is consistent with previous study (Chang et al, 2014;Zhang et al, 2014). MTT assay showed that matrine suppressed the viability of human lung cancer line A549 in dose-and time-dependent manners after cells were treated with matrine at 0.25-4.0 mg/ml for 24, 48, 72 h, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies shown that matrine decreased the percentage of S phase cells, increased the percentage of cells in the G1 phase, accelerated the DNA synthesis process, increased DNA damage and genome instability . Other studies have shown that matrine can block cell cycle in G1 phase, S phase, or G2/M period . The observed synergistic impacts may be caused by either promoting the expression of GADD45B gene or through other signaling pathways such as EGFR/ERK/MMP‐2, AKT/GSK3β/β‐catenin, and PTEN/AKT to inhibit tumor cell progression .…”
Section: Discussionmentioning
confidence: 98%
“…Matrine exerts excellent pharmacological activity and is beneficial for lowering body temperature, promoting diuresis, detoxifying, treating jaundice and preventing liver fibrosis. Previous studies indicated that matrine may be used as an effective treatment for various types of cancer, including liver (21) and lung cancer (22), gastric (23) and colon cancer (24), cervical cancer (25), leukemia (26), osteosarcoma (27), glioma (28) and nasopharyngeal carcinoma (29), and exhibits potent activity against various other types of cancer. Lung cancer occurs in the bronchial epithelium (30) and is characterized by a high morbidity rate (31), a considerable degree of malignancy, a great metastatic propensity in the early stages and the tendency to recur following tumor excision (32).…”
Section: Discussionmentioning
confidence: 99%